THE EFFECT OF SERVICE QUALITY AND PRODUCT VARIATION ON PURCHASING DECISIONS OF USERS OF THE JD.ID ONLINE SHOP APPLICATION - Hidayat P, Farid; Susanto, Denies (Yayasan Education and Social Center, 2025)
This study aims to analyze the influence of Service Quality, Product Variety, Price, Consumer Trust, and Convenience on consumer purchasing decisions. This study uses a quantitative approach and a purposively selected sample of 94 respondents. The analysis techniques used are simple linear regression, multiple linear regression, classical assumption tests, coefficient of determination tests, t-tests, and F-tests, using SPSS version 26. The results of the classical assumption tests indicate that the research data are typically distributed, free of multicollinearity, and free of heteroscedasticity. Simple regression analysis shows that Service Quality and Product Variety have a positive, significant effect on purchasing decisions. The results of multiple linear regression indicate that simultaneously all five independent variables have a positive impact on purchasing decisions with an Adjusted R² of 0.442. The t-test shows that Service Quality, Product Variety, and Price have significant effects individually, while Consumer Trust and Convenience have positive but insignificant impacts. The simultaneous F-test confirms the considerable influence of all independent variables on purchasing decisions. The findings of this study emphasize the importance of managing service quality, product variety, Price, and consumer trust as a strategy to encourage consumer purchasing decisions.